Risk management analysis for novel coronavirus in Wuhan, China - Xiao-Guang Yue; Xue-Feng Shao; Rita Yi Man Li; M. James C. Crabbe; Lili Mi; Siyan Hu; Julien S. Baker; Gang Liang (Journal of Risk and Financial Management, 2020)
Recently, a novel coronavirus pneumonia (2019-nCoV) outbreak occurred in Wuhan, China, rapidly spreading first to the whole country, and then globally, causing widespread concern. From the perspectives of early warning and identification of risk, risk monitoring, and analysis, as well as risk management and handling, we propose corresponding solutions and recommendations, which include institutional cooperation, and to inform national and international policy-makers.
Keywords: 330; 2019-nCoV; coronavirus; pneumonia; risk management; Wuhan